An Exploratory Study of the Effects of Mind–Body Interventions Targeting Sleep on Salivary Oxytocin Levels in Cancer Survivors. (July 2015) - Lipschitz, David L.; Kuhn, Renee; Kinney, Anita Y.; Grewen, Karen; Donaldson, Gary W.; Nakamura, Yoshio
Cancer survivors experience high levels of distress, associated with a host of negative psychological states, including anxiety, depression, and fear of recurrence, which often lead to sleep problems and reduction in quality of life (QOL) and well-being. As a neuropeptide hormone associated with affiliation, calmness, and well-being, oxytocin may be a useful biological measure of changes in health outcomes in cancer survivors. In this exploratory study, which comprised a subset of participants from a larger study, we evaluated ( a ) the feasibility and reliability of salivary oxytocin (sOT) levels in cancer survivors and ( b ) the effects of 2 sleep-focused mind–body interventions, mind–body bridging (MBB) and mindfulness meditation (MM), compared with a sleep hygiene education (SHE) control, on changes in sOT levels in 30 cancer survivors with self-reported sleep disturbance. Interventions were conducted in 3 sessions, once per week for 3 weeks. Saliva samples were collected at baseline, postintervention (~1 week after the last session), and at the 2-month follow-up. In this cancer survivor group, we found that intra-individual sOT levels were fairly stable across the 3 time points, of about 3 months' duration, and mean baseline sOT levels did not differ between females and males and were not correlated with age. Correlations between baseline sOT and self-report measures were weak; however, several of these relationships were in the predicted direction, in which sOT levels were negatively associated with sleep problems and depression and positively associated with cancer-related QOL and well-being. Regarding intervention effects on sOT, baseline-subtracted sOT levels were significantly larger at postintervention in the MBB group as compared with those in SHE. In this sample of cancer survivors assessed for sOT, at postintervention, greater reductions in sleep problems were noted for MBB and MM compared with that of SHE, and increases in mindfulness and self-compassion were observed in the MBB group compared with those in SHE. The findings in this exploratory study suggest that sOT may be a reliable biological measure over time that may provide insight into the effects of mind–body interventions on health outcomes in cancer survivors.